Efficacy in Japanese adults with growth hormone deficiency receiving weekly somapacitan or daily growth hormone: results from phase 3 REAL 1 trial - Otsuka, Fumio; Rasmussen, Michael Højby; Endo, Takaaki; Sværke, Claus; Tahara, Shigeyuki; Johannsson, Gudmundur (Frontiers in Endocrinology, 2025)
IntroductionSomapacitan is a long-acting growth hormone (GH) derivative approved for once-weekly treatment of adult GH deficiency (AGHD). This study aimed to evaluate the efficacy and safety of somapacitan and daily GH in Japanese individuals with AGHD.MethodsThis subgroup study included the 34-week main period of the multinational, randomized, parallel-group, phase 3 trial, REAL 1 (NCT02229851). Participants received once-weekly somapacitan or daily GH (Norditropin®), both administered subcutaneously. Investigators and trial sites were blinded. A total of 36 Japanese GH-naïve individuals with AGHD were allocated to somapacitan or daily GH (excluding the placebo group of the global trial). Endpoints included change in truncal fat percentage to week 34 measured using dual-energy x-ray absorptiometry, as well as other body composition measures. Insulin-like growth factor I standard deviation score values were used for dose titration.ResultsIn total, 36 Japanese individuals were included (18 and 18 in the somapacitan and daily GH group, respectively). 35 completed the main period (34 weeks). Mean (SD) change from baseline to week 34 in truncal fat percentage was -2.23 (2.50) %-points in the somapacitan group and -2.12 (4.21) %-points in the daily GH group. Other body composition measures also improved in both groups, including reduced visceral fat and increased lean body mass. Somapacitan was well tolerated, with a safety profile similar to daily GH.ConclusionsIn Japanese treatment-naïve individuals with AGHD, once-weekly somapacitan demonstrated similar efficacy and safety to daily GH after 34 weeks of treatment. Somapacitan provides an effective alternative to daily GH in AGHD.Clinical trial registrationhttp://www.clinicaltrials.gov, identifier NCT02229851.